Frequency and Correlates of Mycoplasma genitalium Antimicrobial Resistance Mutations and Their Association With Treatment Outcomes: Findings From a National Sentinel Surveillance Pilot in England. Issue 12 (December 2021) - Fifer, Helen; Merrick, Rachel; Pitt, Rachel; Yung, Mandy; Allen, Hester; Day, Michaela; Sinka, Katy; Woodford, Neil; Mohammed, Hamish; Brown, Colin S.; Hughes, Gwenda; Cole, Michelle
Abstract : Background: Mycoplasma genitalium infection is a public health concern due to extensive antimicrobial resistance. Using data from a pilot of M. genitalium antimicrobial resistance surveillance, we determined the prevalence and risk factors for resistance among specimens from sexual health clinic attendees and assessed treatment outcomes. Methods: Seventeen sexual health clinics in England sent consecutive M. genitalium –positive specimens to the national reference laboratory from January to March 2019. Regions of the 23S rRNA, parC, and gyrA genes associated with macrolide and fluoroquinolone resistance, respectively, were amplified and sequenced where appropriate. Fisher exact tests, and univariate and multivariable logistic regression models were used to determine associations between demographic, clinical, and behavioral factors and resistance-associated mutations. Results: More than two-thirds (173 of 249 [69%]) of M. genitalium specimens had mutations associated with macrolide resistance, whereas predicted fluoroquinolone (21 of 251 [8%]) and dual-drug (12 of 237 [5%]) resistance were less prevalent. No specimens had both gyrA and parC resistance-associated mutations. Macrolide resistance was more common in specimens from men who have sex with men compared with heterosexual men (adjusted odds ratio, 2.64; 95% confidence interval, 1.09–6.38; P = 0.03). There was an association between both macrolide and fluoroquinolone resistance and having a previous sexually transmitted infection ( P = 0.06). Only 19% of individuals returned for a test of cure. Of those infected with a macrolide-resistant genotype who were given azithromycin, 57 of 78 (73%) were known or assumed to be clinically cured; however, 43 of these 57 (75%) also received doxycycline. Of the 21 with a macrolide-resistant genotype who failed treatment, 18 of 21 (86%) also received doxycycline. Conclusions: Although macrolide resistance was widespread, particularly among specimens from men who have sex with men and those with a previous sexually transmitted infection diagnosis in the past year, resistance-associated mutations in M. genitalium did not seem to be unequivocally predictive of treatment failure. Abstract : Mycoplasma genitalium antimicrobial resistance surveillance in England showed that more than two-thirds of M. genitalium specimens had mutations associated with macrolide resistance and that resistance was associated with men who have sex with men and previous sexually transmitted infections.